Functional Correlates of Lower Cognitive Test Scores in Essential Tremor - Louis, Elan D. (2010)
BACKGROUND: Although motor features have been the defining element of essential tremor (ET), lower neurocognitive test scores are increasingly being recognized. However, the clinical correlates, if any, of these lower test scores remain largely unexplored. OBJECTIVE: To determine whether cognitive test scores in ET have any functional correlates. METHODS: The Modified Mini Mental Status Examination (MMSE), Katz Activities of Daily Living (ADL) scale and Lawton Instrumental (I) ADL scale were administered to 95 cases. RESULTS: The Katz ADL score (rho = 0.26, p = 0.01) and Lawton IADL score (rho = 0.32, p = 0.001) were correlated with MMSE scores, such that poorer cognitive performance indicated greater dysfunction. Furthermore, cognitive test scores were a better predictor of functional disability than was tremor severity. CONCLUSIONS: Poorer cognitive performance in ET was associated with greater functional deficit. Cognition should enter the clinical dialogue with ET patients as an issue of clinical significance.